2021
DOI: 10.1186/s12871-021-01413-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain treatment with transmuscular quadratus lumborum block and fascia iliaca compartment block in patients undergoing total hip arthroplasty: a randomized controlled trial

Abstract: Background Patients often suffer moderate or even severe pain after total hip arthroplasty; such pain seriously affects early postoperative recovery. This study aimed to investigate the analgesic efficacy of ultrasound-guided transmuscular quadratus lumborum block combined with fascia iliaca compartment block for elderly patients undergoing total hip arthroplasty. Methods Fifty-four patients scheduled for total hip arthroplasty were included in thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Another investigator, namely, independent of group assignment, was responsible for collecting postoperative data. In the end, a statistician carried out the statistical analysis and kept the entire process confidential [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another investigator, namely, independent of group assignment, was responsible for collecting postoperative data. In the end, a statistician carried out the statistical analysis and kept the entire process confidential [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Through the analysis of 569 patients with acetabular fractures, some scholars reported that the overall incidence of postoperative traumatic arthritis was 17%, of which the incidence of complete reduction was 10% and that of incomplete reduction was 35% [ 6 ]. Many literatures have pointed out that the postoperative effect is not satisfactory, which is often accompanied by joint dislocation, marginal compression, and ipsilateral femoral head fracture such as in the initial operation, which failed to fix the fracture, the necessary bone graft treatment, and often bring about serious complications [ 7 ]. Based on this, this study analyzed the risk factors of traumatic arthritis after THA in the treatment of acetabular fractures by logistic regression and promoted the clinical treatment methods to provide theoretical basis for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al. ( 19 ) showed that using a single anterior QLB in knee arthroplasty significantly reduced postoperative opioid consumption and improved postoperative recovery scores. This discrepancy in results is most likely due to different approaches of QLB and local anesthetic doses.…”
Section: Discussionmentioning
confidence: 99%
“…Kwak et al (10) pointed out that using a single lateral QLB in laparoscopic partial nephrectomy can reduce postoperative opioid consumption, but the quality of recovery score at 48 h after surgery was not significantly different from that of the control group. Xia et al (19) showed that using a single anterior QLB in knee arthroplasty significantly reduced postoperative opioid consumption and improved postoperative recovery scores. This discrepancy in results is most likely due to different approaches of QLB and local anesthetic doses.…”
Section: B Amentioning
confidence: 99%